Psychopathy and Positive and Negative Affect Schedule (PANAS) as Predictors of Totalitarian Political Ideology - Šram, Zlatko (Psihološka istraživanja, 2020)
The present study had two goals: First was to find out whether the high need for government-imposed security and social regulation, acceptance of living in a dictatorship, limitations, and denial of individual freedom, supporting the repressive methods and procedures are in such high mutual correlations that they form a coherent latent dimension of Totalitarian Political Ideology (TPI). Second, to find out whether and which of the psychopathy traits (Interpersonal, Affective, Lifestyle, and Antisocial) and the PANAS (Positive and Negative Affect Schedule as a measure of general affectivity) are underlying Totalitarian Political Ideology. A convenience sample of the undergraduate and graduate students from the University of Zagreb was selected on which research was carried out. In order to explore how psychopathic traits and positive and negative affect have an impact on the internalization of Totalitarian Political Ideology (TPI), multiple regression analysis was conducted. It was found out that Totalitarian Political Ideology represents an internally coherent and reliable pattern of political orientations and values. Interpersonal manipulation, Callous affect, and Negative affect were significant predictors of the TPI scale in positive directions, whereas Erratic lifestyle was a significant predictor of the TPI scale in the negative direction. About 13% of the variance of Totalitarian Political Ideology was explained by these personality characteristics. The findings can have both theoretical and practical contributions in understanding the endorsement of totalitarian beliefs.